Effects of breast cancer on chronic disease medication adherence among older women. Issue 8 (15th February 2016) - Santorelli, Melissa L.; Steinberg, Michael B.; Hirshfield, Kim M.; Rhoads, George G.; Bandera, Elisa V.; Lin, Yong; Demissie, Kitaw
Abstract: Purpose: The purpose of this study was to determine the effects of breast cancer on chronic disease medication adherence among older women. Methods: The Surveillance, Epidemiology, and End Results (SEER)‐Medicare‐linked data and a 5% random sample of Medicare enrollees were used. Stage I–III breast cancer patients diagnosed in 2008 and women without cancer were eligible. Three cohorts of medication users 66+ years were identified using diagnosis codes and prescription fill records: diabetes, hypertension, and lipid disorders. For each cohort, breast cancer patients were frequency matched to comparison women by age and geographic area. Medication adherence was measured by the proportion of days covered and medication persistence. Results: During the post‐baseline period, the percentage of breast cancer patients who were non‐adherent was 26.2% for diabetes medication, 28.9% for lipid‐lowering medication, and 14.2% for hypertension medication. Breast cancer patients experienced an increased odds of diabetes medication non‐adherence [odds ratio (OR) = 1.44; 95% confidence interval (CI) = 1.07 to 1.95] and were more likely to be non‐persistent with diabetes medication (hazard ratio = 1.31; 95%CI: 1.04 to 1.66) relative to women without cancer. The study failed to show a difference between breast cancer and comparison women in the odds of non‐adherence to hypertensive (OR = 0.87; 95%CI: 0.71 to 1.05) or lipid‐lowering medication (OR = 0. 91; 95%CI: 0.73 to 1.13) with a proportion of days covered threshold of 80%. Conclusion: Special attention should be given to the coordination of primary care for older breast cancer patients with diabetes. Copyright © 2016 John Wiley & Sons, Ltd.